Higher production of C-phycocyanin by nitrogen-free (diazotrophic) cultivation of Nostoc sp. NK and simplified extraction by dark-cold shock. (March 2017) - Lee, Na Kyeong; Oh, Hee-Mock; Kim, Hee-Sik; Ahn, Chi-Yong
Highlights: C-PC content in Nostoc sp. NK increased in diazotrophic cultivation. C-PC content increased under red light lamp by complementary chromatic adaptation. Nostoc sp. NK in diazotrophic culture released C-PC spontaneously under dark at 5 °C. Abstract: Nostoc sp. NK (KCTC 12772BP) was isolated and cultivated in a BG11 medium and a nitrate-free BG11 medium (BG110 ). To enhance C-phycocyanin (C-PC) content in the cells, different fluorescent lamps (white, plant, and red) were used as light sources for complementary chromatic adaptation (CCA). The maximum biomass productivity was 0.42 g/L/d and 0.32 g/L/d under BG11 and BG110 conditions, respectively. The maximum C-PC contents were 8.4% (w/w) under white lamps, 13.6% (w/w) under plant lamps, and 18% (w/w) under BG110 and the red light condition. The maximum C-PC productivity was 57.4 mg/L/d in BG110 under the red lamp condition. These results indicate that a higher C-PC content could be obtained under a diazotrophic condition and a CCA reaction. The C-PC could be released naturally from cells without any extraction processes, when Nostoc sp. NK was cultivated in the BG110 medium with CO2 aeration and put in dark conditions at 5 °C.